METHODS OF MANAGEMENT OF FINANCING IN FIXED CAPITAL OF THE ENTERPRISE - E. Dzhamay; A. Zinchenko; M. Bobrova (Вестник университета)
In work methods of an investment of financial resources in fixed capital of the domestic enterprise were investigated. Two directions of acquisition of the new equipment are considered: with use of the mechanism of leasing and with attraction of credit resources. By results of the carried-out calculations the conclusion is drawn that under equal financing terms leasing is most favorable as payments for the credit significantly exceed payments on leasing.